PTH-133 Nutrition Training in UK Medical Undergraduate Programmes – Has The Situation Improved?. (17th August 2016) - Long, W; Neild, P
Abstract : Introduction: Nutrition education in medical schools has historically been neglected and found to be inadequate. 1 Programmes designed to improve nutrition training have shown increased student knowledge. 2, 3 The aim of this study was to survey current nutrition training provided by UK medical schools. Methods: A 14 item questionnaire was sent to academics representing all UK medical schools on a national undergraduate nutrition education implementation group. . Data was analysed using SPSS version 21.0 and significance determined using a 2 tailed Fischer's exact test. Results: The response rate was 34%(11of 32). Students' knowledge was assessed in 8 of 11 (73%) medical schools. The mean total time devoted to nutrition was 18.4 hrs (range 4 to 40+). 7/10 included all 4 core nutrition topics in their curriculum. 3/9 had a nutrition thread throughout their curriculum and 5/10 had a named nutrition lead. Only 3/9 perceived that their training was adequate. Of those 3, all cited ''increased formal teaching time devoted to nutrition' and 'better organisation of the nutrition teaching' as improvements that facilitated adequate training. Of those who reported inadequate training, 83% cited 'lack of prioritisation' and 67% cited 'unable to devote more teaching time to nutrition' and 'difficulty organising topics and teaching sessions' as hindrances towards improving training. The presence of a nutrition lead was associated with a trend to greater mean total time allocated to structured teaching (25.4 vs 16.2 hours) and greater likelihood of teaching all four core areas (5/5 vs 2/5, p = 0.08). Conclusion: Indicators of good training appear to be more common in courses placing a higher priority on nutrition, including the presence of a named nutrition lead. Despite a decrease in the % of respondents reporting adequate training compared to a previous study in 20091 1 (33% vs 50%), indicators of good training appear to have increased. This may reflect increased awareness of the standards required as a result of the development of a standardised national nutrition curriculum, signposted in the 2009 edition of 'Tomorrow's Doctors'. 4 References: 1 Johnston R, Neild P, Jeanes Y, Bowling T. Nutrition training in UK medical undergraduate programmes. Proceedings of the Nutrition Society 2009;68 :(OCE1). 2 Maher B, Sweeney C, O'Tuathaigh C, O'Flynn S, Brown, J. Evaluation of a novel nutrition education intervention for medical students. Proceedings of the Nutrition Society 2013;72 :(OCE3). 3 Taren D.Effect of an integrated nutrition curriculum on medical education, student clinical performance, and student perception of medical-nutrition training. American Journal of Clinical Nutrition 2001;73: 1107–1112 4 GMC. Tomorrow's Doctors. London 2009; http://www.aormc.uk.ore/static/documents/content/TomorrowsDoctors2009pdf . Disclosure of Interest: None Declared